THE USE OF ICT N EFL CLASSROOM - Ozah Faoziah; Ida siti Jubaedah; Abdul Kodir; Eva Fitriani Syarifah (Universitas Majalengka, 2019)
The aim of this paper was to explore the types of ICT that teacher implemented in EFL classroom at senior high school in Majalengka regency. Besides, the problem might arise on the use of ICT in ELT. In addition, the researcher investigated the trouble towards the use of ICT in EFL classroom. This study used the descriptive method to reveal the research problems. The interview and observation is used to collect the data. The study showed that (1) The types of ICTs that teachers use in EFL Classroom are set of computer (language lab), PowerPoint (PPT), and some applications such as Edmodo, the group of WA (Whatsapp), YouTube apps, Padlet and Kahoot; (2) The obstacles that teachers faced in using ICTs is less participation - not all students have the smartphone, technical-based problem had biggest obstacle which lack of facilities from the school.